Range Extension of Bull Trout, Salvelinus confluentus, to the Central Northwest Territories, with Notes on Identification and Distribution of Dolly Varden, Salvelinus malma, in the Western Canadian Arctic - Reist, James D.; Low, George; Johnson, James D.; McDowell, Don (ARCTIC, 2002)
The presence of bull trout (Salvelinus confluentus) is reported from four locations in the Sahtu Settlement Area of the Northwest Territories centered about 64°30'N and 125°00'W. These reports extend the geographical range of this species approximately 500 km north of the previous northernmost published localities in the southern Northwest Territories (~61°N, 125°W, Prairie Creek, Liard River drainage). The identity of these char is confirmed using quantitative criteria in a linear discriminant function from the literature shown to be 100% effective in distinguishing bull trout from Dolly Varden (S. malma). Regular captures of these fish at one location over several years indicate that these records likely represent established populations and not extralimital occurrences. We hypothesize that bull trout are more extensively distributed in high-gradient streams and rivers of the south-central Mackenzie River valley and likely also occur north of this area. Only limited scientific work has been done in the area, and data on taxonomy and distributions of species are generally lacking. In much of the previous literature, reports of char (other than lake trout, S. namaycush) have identified the fish as Dolly Varden or arctic char (S. alpinus). These identifications are suspect, and care must be taken when interpreting such literature. The presence and vulnerability of bull trout present significant challenges for their conservation and management in this area. On a rapporté la présence de l'omble à tête plate (Salvelinus confluentus) à quatre endroits de l'établissement du Sahtu (Territoires du Nord-Ouest), dont la position est environ 64° 30' de lat. N. et 125° 00' de long. O. Ces rapports prolongent l'habitat de cette espèce d'environ 500 km au nord des lieux les plus septentrionaux mentionnés précédemment dans la documentation, lieux situés dans la partie sud des Territoires du Nord-Ouest (~ 61° de lat. N., 125° de long. O., bassin de la Liard). L'identité de ces ombles est confirmée grâce à l'utilisation de ...